1998
DOI: 10.1016/s0006-3495(98)77913-5
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfers in the B808–866 Antenna from the Green Bacterium Chloroflexus aurantiacus

Abstract: Energy transfers within the B808-866 BChl a antenna in chlorosome-membrane complexes from the green photosynthetic bacterium Chloroflexus aurantiacus were studied in two-color pump-probe experiments at room temperature. The steady-state spectroscopy and protein sequence of the B808-866 complex are reminiscent of well-studied LH2 antennas from purple bacteria. B808-->B866 energy transfers occur with approximately 2 ps kinetics; this is slower by a factor of approximately 2 than B800-->B850 energy transfers in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…sphaeroides; our findings substantiate a circular model for the LHB800-880-RC assembly such that the circle of about 32 ± 1 interacting BChl a molecules are coupled to the low exciton transition of the reaction center primary donor P . This arrangement is similar to that proposed in the work of Novoderezhkin et al (1998). A similar circular arrangement of the LH antenna around the RC in Rf.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…sphaeroides; our findings substantiate a circular model for the LHB800-880-RC assembly such that the circle of about 32 ± 1 interacting BChl a molecules are coupled to the low exciton transition of the reaction center primary donor P . This arrangement is similar to that proposed in the work of Novoderezhkin et al (1998). A similar circular arrangement of the LH antenna around the RC in Rf.…”
Section: Resultssupporting
confidence: 84%
“…One model for the light-harvesting antenna LHB808-866 complex of Cf. aurantiacus has been proposed by Novoderezhkin et al (1998). In that model, two concentric aggregates are considered that lie in two planes parallel to the membrane plane; the first consists of 24-32 BChl 866 strongly coupled molecules, in which the strongest interactions are between dimers, the second ring consists of 12-18 BChl 808 weakly coupled molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy transfer between the 808 and 866 nm bands was studied by picosecond fluorescence decay and was found to have an equilibration time of 5 ps (Griebenow et al 1991). The results obtained by femtosecond differential absorption study showed that this energy transfer occurs with $2 ps kinetics in whole chlorosome-membrane complexes (Novoderezhkin et al 1998). We have recently investigated the excitation energy transfer processes between the carotenoids and BChls in isolated core complexes (Montan˜o et al 2004) and found that the low efficiency of energy transfer is probably due to that only the carotenoid S 1 excited state is involved.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, our earlier pump-probe experiments on CMC, isolated from the similar Cfx. aurantiacus cell culture C-8, strongly suggest that the entire BChl a band with absorption maximum at *805 nm (which is a superposition of the B798 and B808 BChl a bands) is due to pigments, functioning essentially as monomeric ones (Novoderezhkin et al 1998b). In addition, the shape of the BChl a DA spectrum fully reproduces the shape of the B798 steady-state absorption spectrum.…”
Section: Room-temperature Measurementsmentioning
confidence: 98%